8
Аноним
Математика
09 марта 12:24

(х-1 15/16)+7 3/16=8 1/16+4 9/16

Ответ или решение1

Решим уравнение:

(х - 1 15/16) + 7 3/16 = 8 1/16 + 4 9/16;

8 1/16 + 4 9/16 = 8 + 4 + 1/16 + 9/16 = 12 + 1/16 + 9/16 = 12 + (1 + 9)/16 = 12 + 10/16 = 12 + 5/8 = 12 5/8;

(х - 1 15/16) + 7 3/16 = 12 5/8;

х - 1 15/16 = 12 5/8 - 7 3/16;

12 5/8 - 7 3/16 = 12 - 7 + 5/8 - 3/16 = 5 + 10/16 - 3/16 = 5 + (10 - 3)/16 = 5 + 7/16 = 5 7/16;

х - 1 15/16 = 5 7/16;

х = 5 7/16 + 1 15/16;

5 7/16 + 1 15/16 = 5 + 1 + 7/16 + 15/16 = 6 + 7/16 + 15/16 = 6 + (7 + 15)/16 = 6 + 22/16 = 6 + 1 6/16 = 7 6/16 = 7 3/8.

х = 7 3/8.

Ответ: х = 7 3/8.

0 / 10000
ВходРегистрация

Вход

или

Регистрация